2018
DOI: 10.1099/ijsem.0.002491
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium godavarianum sp. nov., isolated from the Godavari river, India

Abstract: A Gram-stain-positive, rod-shaped, non-motile bacterium, strain PRD07, was isolated from Godavari river, India during the world's largest spiritual and religious mass bathing event 'Kumbh Mela'. Molecular analysis using 16S rRNA gene sequencing and phylogenetic analysis reveals the distinct phylogenetic positioning of strain PRD07 within the genus Corynebacterium. The strain demonstrated highest sequence similarity to Corynebacterium imitans DSM 44264 (97.9 %), Corynebacterium appendicis DSM 44531 (97.1 %) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…23 21 Bacterial load in the river increased by approximately 130 fold. 12,[24][25][26][27][28][29] At the 2013 Kumbh Mela, a study 15,16,20 that followed 30 000 pilgrims in four sector hospitals found a 5% incidence of diarrhoeal diseases over a 23day period. A rise in nonbloody diarrhoea cases was seen just 2 days after the main bathing day on Jan 29, 2013, and a peak in upper respiratory tract infections coincided with the peak in nonbloody diarrhoeal disease.…”
Section: Infectious Diseases Transmission At the Kumbh Melamentioning
confidence: 99%
See 1 more Smart Citation
“…23 21 Bacterial load in the river increased by approximately 130 fold. 12,[24][25][26][27][28][29] At the 2013 Kumbh Mela, a study 15,16,20 that followed 30 000 pilgrims in four sector hospitals found a 5% incidence of diarrhoeal diseases over a 23day period. A rise in nonbloody diarrhoea cases was seen just 2 days after the main bathing day on Jan 29, 2013, and a peak in upper respiratory tract infections coincided with the peak in nonbloody diarrhoeal disease.…”
Section: Infectious Diseases Transmission At the Kumbh Melamentioning
confidence: 99%
“…27 A novel antibioticresistant bacterial species, Corynebacterium godavarianum, has been isolated from the bathing site of the Godavari River. 25 In response to this growing global concern, 28 an expert panel concluded that use of antibiotics should be restricted to acute travellers whose diarrhoea is incapacitating. 30…”
Section: Emergence and Transmission Of Antibiotic-resistant Bacteria mentioning
confidence: 99%
“…In January 2018, Jani et al described Corynebacterium godavarianum sp. nov., an isolate recovered from the fresh-water Godavari River in south-central India during a religious mass bathing event, the 'Kumbh Mela' [2]. This bacterium had ~99.2-99.9 % similarity to the Canadian strains and 99.3 % to C. gottingense by 16S rRNA gene sequencing, as well as >99 % similarity by rpoB sequencing to the Canadian strains.…”
mentioning
confidence: 99%
“…Cellular fatty acid (CFA) composition analysis had been done for most Canadian isolates after growth for 48 h at 35 °C in 5 % CO 2 on Columbia Base agar with 5 % sheep blood (SBA), as described previously [13]. CFAs for six Canadian isolates, C. gottingense, C. godavarianum and C. hadale [1][2][3] were consistent with those described for the genus; that is, longchained cellular fatty acids of the straight-chain saturated and monounsaturated types, with significant amounts of hexadecanoic (palmitic, C 16 : 0 ), octadecanoic (C 18 : 0 ), and cis-9-octadecenoic (C 18 : 1 ω9c) acids as major components [14] (also summarized in Table S2).…”
mentioning
confidence: 99%
See 1 more Smart Citation